118 Molecular and Immunological Landscape of the Pleomorphic Xanthoastrocytoma–Epithelioid Glioblastoma Spectrum - Iman Dandapath; Swati Mahajan; Jyotsna Singh; Mehar Chand Sharma; Chitra Sarkar; Vaishali Suri (Neuro-Oncology, 2026)
Abstract Background Pleomorphic xanthoastrocytoma (PXA), especially PXAG3, exhibits considerable morphologic, molecular, and clinical overlap with epithelioid glioblastoma (eGB), raising questions regarding their biological relationship and progression dynamics. Although immune checkpoint pathways have been investigated in glioblastoma, comprehensive integration of immune profiling with transcriptomic signatures across the PXA–eGB spectrum remains inadequately defined. Methods Fifty-three tumors (PXAG2 n = 15, PXAG3 n = 6, eGB n = 14, IDH-wildtype GB n = 18) underwent histopathologic review, molecular profiling (BRAF, CDKN2A, EGFR), immune checkpoint assessment (PD-L1, CTLA-4, CD3, CD8), mRNA expression array, qRT-PCR validation, multiplex immunofluorescence, and functional siRNA assays. Results PXA and eGB predominantly affected pediatric and young adult patients, IDH-wildtype GB occurred mainly in older adults. Both PXA and eGB exhibited an immune-enriched phenotype compared with IDH-wildtype GB, with significantly higher CTLA-4 expression (p = 0.001) and greater CD3+ TIL density in PXA (PXA vs eGB p = 0.015; PXA vs GB p < 0.0001). BRAF V600E mutations were frequent in PXAG2 (66.7%) and eGB (50%), whereas EGFR amplification predominated in IDH-wildtype GB (66.6%). Gene expression profiling identified RUNX1 and IGFBP2 upregulation in eGB and IDH-wildtype GB. MS4A4E was overexpressed across subtypes, highest in PXA (p = 0.007), with significantly greater MS4A4E-positive T-cell density in PXA (p = 0.014 vs eGB; p < 0.0001 vs GB) on multiplex fluorescence imaging. Higher MS4A4E expression correlated with improved progression-free survival (p = 0.023). Conclusion PXA and eGB represent an immune-enriched glioma spectrum molecularly distinct from IDH-wildtype GB. While BRAF-driven alterations characterize the PXA–eGB spectrum and EGFR amplification defines conventional GB, RUNX1 and IGFBP2 reflect tumor-intrinsic oncogenic programs in high-grade gliomas. In contrast, MS4A4E delineates a T-cell–associated microenvironment, particularly in PXA, supporting microenvironment-based stratification within this continuum.